Deciphering gut pathology, oxidative stress, metabolome and microbiome alterations in javanese medaka fish (Oryzias javanicus Bleeker, 1854) exposed to polystyrene microplastics - Usman, Sunusi (2022)
Microplastics (MPs) defined as plastics of less than 5mm in size have become pollutants of concern due to their continuous and unregulated release into the environment, making them readily accessible to a wide range of aquatic organisms and easily transferred across the food web. Their ever-present nature has led to human exposure largely through food and drinking water, with unrevealed health implications. Animal studies, in most instances, heavily relate its effects to the mere accumulation and induction of oxidative stress and inflammation in the gut system with other organs not well studied. Recently, a few studies on the exposure effects of MPs on the gut have reported bacterial microbiome and metabolome perturbations, which need to be explored further. This study hypothesised that polystyrene microplastics (PS-MPs) exposure induces organs histological alterations, gut oxidative stress and increase permeability, brain oxidative stress, oxidant damage and neurotoxicity and gut microbiome and metabolome alterations in Javanese medaka fish. The goal of the study is to determine the exposure of effects of PS-MPs on organs histopathology, gut oxidative stress and permeability, brain oxidative stress, oxidant damage, and neurotoxicity, and gut microbiome and metabolome alterations. Javanese medaka fish were exposed to polystyrene microplastics (PS-MPs) suspensions for a period of 21 days at concentrations of 100μg/L (MP-LOW), 500μg/L (MP-MED) and 1000μg/L (MP-HIGH). The gut and other organs were evaluated for histological alterations, oxidative stress, permeability, and neurotoxicity. Furthermore, gut metabolome and microbiome alterations were assessed. Histological features of inflammation and tissue damage was found in the PS-MPs exposed groups, but none in the control, with significant difference (p-value < 0.05) found between the three exposure concentrations in the intestines [MP-HIGH (74 ± 6%), MP-MED (54 ± 6%) and MP-LOW (26 ± 5%)], Liver [MP-HIGH (86 ± 3%), MP-MED (60 ± 5%) and MP-LOW (46 ± 3%)] and the kidney [MP-HIGH (66 ± 4%), MP-MED (26 ± 5%) and MP-LOW (14 ± 4%)]. Intestinal permeability assessed by D-Lactate in nmol/mL [Control (38 ± 20), MP-LOW (60 ± 2), MP-MED (67 ± 2), MP-HIGH (78 ± 2)], and intestinal oxidative stress using catalase (CAT) in U/mg protein [Control (191 ± 22), MP-HIGH (29 ± 17)] and total superoxide dismutase (T-SOD) activity in U/mg of protein [Control (61.8 ± 5), MP-HIGH (43 ± 4)] were found to be significantly increased. In the brain, a significant increase in oxidative stress [CAT activity, Control (16±3), MPHIGH (6 ±1) and T-SOD activity (Control (67 ± 18), MP-HIGH (38 ± 5)], oxidant damage measured using MDA in ng/mL [Control (30.8 ± 2), MP-LOW(47 ± 2), MPMED (55 ± 3), MP-HIGH (38.8 ± 50)], and neurotoxicity by inhibition of acetylcholinesterase in ng/mL [Control (8 ± 0.1), MP-MED (6 ± 1), MP-HIGH (5 ± 1)] was elicited. High throughput sequencing of the bacterial 16S rRNA gene V3-V4 region and fungal ITS2 region, revealed reduction in richness and diversity of the gut microbiome. The top 5 relative abundance of bacterial phyla showed increase in Proteobacteria from 65% in the control to 79% in the MP-LOW and MP-MED groups, and 88% observed in MP-HIGH. Conversely, Actinobacteriota showed a decline from 22% in the control group to 9%, 10% and 6% in the low, medium and highest PS-MPs exposed groups respectively. A total number of 7 bacterial biomarkers including g_Aeromonas as unique feature in the MP-HIGH group, and g_Ralstonia, g_ Paraburkholderia, g_Pelmonas, g_Staphylococcus, g_Bradyrhizobium, and g_Pararhizobium were found as the unique features in the MP-LOW group. The top 5 fungal phyla relative abundance showed a reduction of Ascomycota and Chytridiomycota from 42% and 48% in the control to 30% and 40% respectively in MPMED group, and 24% and 21% in MP-HIGH group. 1H NMR metabolomics revealed 9 metabolites responsible for metabolomic alteration due to PS-MPs exposure including anserine, glucose, creatine, glucuronate, glutamate, alanine, lactate, valine, and 2- hydroxyvalerate. The glucose and lactate showed a statistically significant increase with glucose having more than a fourfold increase (Log 2 fold change >2) in all the PS-MPs exposed groups and lactate having more than twofold increase (Log 2 fold change >1) in MP-MED and MP-HIGH exposed groups. The metabolomic pathway analysis revealed the enriched metabolites to be related to energy metabolism via tricarboxylic acid cycle (TCA), creatine pathway and urea cycle. Furthermore, positive correlation was found between the genus Aeromonas and glucose, lactate and creatine metabolites. The results revealed that P S-MPs exposure causes histopathological alterations in the gut and other vital organs including the brain, it causes significant increase in gut oxidative stress and permeability, brain oxidative stress, oxidant damage, as well as neurotoxicity. In the same vein, PS-MPs exposures causes significant alterations in gut bacterial and fungal microbiome both in terms of relative abundance, reduction in species richness and diversity, and differential enrichment of certain clades of the gut microbiome. Furthermore, it led to the alteration of the gut metabolites, by upregulation of glucose, lactate and amino acids. The altered gut microbiome and metabolome are related to hypoxia, inflammation, tissue injury and metabolic disorders. This study have provided additional data on gut bacterial and fungal clades, as well as metabolites associated with MPs toxicity in aquatic organism, this will inevitably enable further exploration, identification of biomarkers, and future health risks associated with MPs exposure in aquatic organisms and possibly humans.